Platelet-derived growth factor-C and -D in the cardiovascular system and diseases. (August 2018) - Lee, Chunsik; Li, Xuri
Abstract: The cardiovascular system is among the first organs formed during development and is pivotal for the formation and function of the rest of the organs and tissues. Therefore, the function and homeostasis of the cardiovascular system are finely regulated by many important molecules. Extensive studies have shown that platelet-derived growth factors (PDGFs) and their receptors are critical regulators of the cardiovascular system. Even though PDGF-C and PDGF-D are relatively new members of the PDGF family, their critical roles in the cardiovascular system as angiogenic and survival factors have been amply demonstrated. Understanding the functions of PDGF-C and PDGF-D and the signaling pathways involved may provide novel insights into both basic biomedical research and new therapeutic possibilities for the treatment of cardiovascular diseases.